High-speed AFM height spectroscopy reveals µs-dynamics of unlabeled biomolecules. Issue 1 (December 2018) - Heath, George; Scheuring, Simon
Abstract Dynamics are fundamental to the functions of biomolecules and can occur on a wide range of time and length scales. Here we develop and apply high-speed AFM height spectroscopy (HS-AFM-HS), a technique whereby we monitor the sensing of a HS-AFM tip at a fixed position to directly detect the motions of unlabeled molecules underneath. This gives Angstrom spatial and microsecond temporal resolutions. In conjunction with HS-AFM imaging modes to precisely locate areas of interest, HS-AFM-HS measures simultaneously surface concentrations, diffusion coefficients and oligomer sizes of annexin-V on model membranes to decipher key kinetics allowing us to describe the entire annexin-V membrane-association and self-assembly process in great detail and quantitatively. This work displays how HS-AFM-HS can assess the dynamics of unlabeled bio-molecules over several orders of magnitude and separate the various dynamic components spatiotemporally. The dynamics of biomolecules can occur over a wide range of time and length scales. Here the authors develop a high-speed AFM height spectroscopy method to directly detect the motion of unlabeled molecules at Angstrom spatial and microsecond temporal resolution.